Organosiloxane composition and application thereof

By introducing silica of different shapes into the material and utilizing the good compatibility of silicone polymers with polypropylene, a new material with high tensile strength and impact strength is prepared, which solves the limitations of material properties and large-scale preparation problems in the prior art.

CN119798855AInactive Publication Date: 2025-04-11德凯新材料(浙江海宁)有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510035556.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to prepare bionic materials with high tensile strength and impact strength on a large scale, and traditional synthesis methods are prone to rupture of molecular structures and difficult to ensure a controllable molecular weight.

Method used

By drawing on the bionic material "brick-sludge" structure, different shapes of silica are introduced, and the good compatibility between silicone polymer and polypropylene is used to prepare a new material with high performance through physical blending.

Benefits of technology

The material preparation with a tensile strength of 3 times that of polypropylene and a shock resistance of 6.9 times that of polypropylene is achieved, which avoids the cost pressure brought by complex polypropylene grafting technology and solves the problem that bionic material preparation technology is difficult to industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798855A_ABST
    Figure CN119798855A_ABST
Patent Text Reader

Abstract

The invention relates to the field of chemical materials, discloses an organosiloxane composition and application thereof, and particularly discloses a formula of the siloxane composition and a preparation method of a siloxane polymer, and the siloxane composition comprises the following components in percentage by weight: 10-20% of silicon dioxide, 20-50% of the siloxane polymer, 30-69% of polypropylene, 0.1-0.4% of an antioxidant and 0.6-0.9% of a lubricant. According to the invention, by referring to the'brick-mud 'structure of a biomimetic material, silicon dioxide in different shapes is introduced into the formula, and the components in the formula are perfectly bridged through good compatibility between the siloxane polymer and polypropylene, so that a novel material with the tensile strength being 3 times that of polypropylene and the impact strength being 6.9 times that of polypropylene is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical materials, and more specifically discloses an organosiloxane composition and application thereof. Background Art

[0002] Siloxane is the most produced, widely used and most widely researched class of organic silicon compounds, accounting for more than 90% of the total use of organic silicon materials. Siloxane substances use silicon oxygen bonds (-Si-O-Si-) as the skeleton, and the side chains can be composed of siloxane groups, hydroxyl groups and aromatic groups of different lengths. They can also be fixed on large molecular rigid substances through covalent bonds. The bond energy of its silicon oxygen bond is greater than the carbon oxygen bond and carbon carbon bond in general organic matter, the intermolecular force is small, and the side chain has high surface activity, and has the properties of both organic and inorganic materials, which makes it a bridge compound for the combination of inorganic and organic materials. This structure gives polysiloxane many excellent properties, such as corrosion resistance, high heat resistance, electrical insulation, radiation resistance, as well as physiological inertness, biocompatibility, and high air permeability, which occupies an important position in many fields.

[0003] In order to meet the increasingly high requirements for the performance of functional materials in different fields, material scientists have conducted a lot of scientific research and exploration in the design and synthesis of siloxane compounds, reaction mechanisms, and physical and chemical properties. Organic and inorganic silicon oxygen functional materials mainly have one-dimensional linear structures, two-dimensional nonlinear structures, three-dimensional polyhedral oligomeric silsesquioxanes, and organic / inorganic hybrid siloxane compounds. Traditional synthesis methods mainly prepare silicon oxygen functional materials through polycondensation, but it is easy to cause molecular structure rupture and it is difficult to ensure controllable molecular weight. A lot of work has been done in the development of new methods. Although some progress has been made, it is still not perfect.

[0004] At present, the synthesis and invention cycle of new functional materials has become longer, and the mechanical properties of many artificially synthesized materials have reached their limits. The new composite materials obtained by fine tailoring of the microstructure can not only break through the performance limit of a single material, but also adjust the material properties as needed, providing a new research direction for the development of materials science. As for the tailoring design of the material microstructure, natural biological structural materials provide people with a rich and effective structural reference template. In the process of natural selection and evolution, biological structural materials show excellent mechanical properties of stiffness, strength, toughness and impact resistance, which is far from the traditional engineering materials, and bionic materials have emerged. However, biological structural materials can often use extremely limited resources to obtain biological material structures with specific directional advantages through the synergistic effect of complex three-dimensional microstructures and multiple toughening mechanisms. At present, the degree of toughness improvement of bionic structural materials compared with their components is still difficult to reach the superior level of biological structural materials. The more prominent problem is that it is still difficult to prepare functional materials on a large scale through this method, which cannot meet market demand. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide an organosiloxane composition material and its application; another purpose of the present invention is to provide a method for preparing a siloxane polymer.

[0006] Technical solution: The organic siloxane composition comprises, by weight, 10-20% silicon dioxide, 20-50% siloxane polymer, 30-69% polypropylene, 0.1-0.4% antioxidant, and 0.6-0.9% lubricant; wherein the structural formula of the siloxane polymer is:

[0007]

[0008] Preferably, the silicon dioxide is in the form of flakes and powder, wherein the mass ratio of flakes to powder is 70-90:10-30.

[0009] Preferably, the diameter of the flaky silicon dioxide is 4-8 micrometers, the thickness is 0.3-1 micrometer, and the particle size D90 of the powdered silicon dioxide is 200-600 nanometers.

[0010] Preferably, the antioxidant is one or a combination of antioxidant 1010, antioxidant DLTP, and antioxidant 168.

[0011] Preferably, the lubricant is a fatty acid or a fatty acid salt.

[0012] A method for preparing a siloxane polymer comprises the following steps:

[0013] S1. Add tetraphenyltetramethylcyclotetrasiloxane and tetramethyldivinyldisiloxane into a reactor, start stirring, and react under reduced pressure at 50-60 degrees Celsius for 1-2 hours while passing nitrogen to remove moisture in the system.

[0014] S2. Add an organic base catalyst to the reactor in step S1, raise the temperature to 70-90 degrees Celsius, react for 1-3 hours, then raise the temperature to 110-120 degrees Celsius, and react under reduced pressure for 2-3 hours to obtain a reaction solution.

[0015] S3, raising the temperature of the reaction solution in step S2 to 140-150 degrees Celsius, removing unreacted materials by evaporation under reduced pressure, and then cooling the reaction product to room temperature to obtain a siloxane polymer.

[0016] Preferably, in step S1, the molar ratio of tetraphenyltetramethylcyclotetrasiloxane to tetramethyldivinyldisiloxane is 80-95:5

[0017] Preferably, in step S2, the organic base is one of tetramethylammonium hydroxide and phosphazene base.

[0018] The organosiloxane composition is used in automobile die castings, circuit board insulation materials, organosilicon packaging materials, and electrical insulation materials.

[0019] Beneficial effects: The present invention draws on the "brick-mud" structure of bionic materials, introduces silica of different shapes into the formula, and perfectly bridges the formula components through the good compatibility between siloxane polymer and polypropylene. A new material with a tensile strength that is 3 times that of polypropylene and an impact strength that is 6.9 times that of polypropylene can be prepared in large quantities by a simple physical blending method, thereby avoiding the cost pressure brought by complex polypropylene grafting technology and solving the problem that bionic material preparation technology is difficult to industrialize and mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0021] Figure 1 This is a scanning electron microscope image of the silicon dioxide agglomerates in Material 1 prepared in Example 4.

[0022] Figure 2 This is a scanning electron microscope image of material 1 prepared in Example 4. DETAILED DESCRIPTION

[0023] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0024] Example 1

[0025] Weigh 544.9 g of tetraphenyltetramethylcyclotetrasiloxane and 10.4 g of tetramethyldivinyldisiloxane, add them into a 1L dry and clean three-necked flask, start stirring, evacuate with a vacuum pump, and introduce dry nitrogen at the same time, heat to 55 degrees Celsius and react for 2 hours; add 2.7 g of tetramethylammonium hydroxide to the reaction system, heat to 80 degrees Celsius, continue to react for 3 hours, then heat to 110 degrees Celsius and react for 3 hours; heat the reaction system to 140 degrees Celsius, distill under reduced pressure until no liquid drips out, continue distillation for 0.5 hours, and obtain 312.3 g of siloxane polymer.

[0026] Example 2

[0027] Weigh 544.9 g of tetraphenyltetramethylcyclotetrasiloxane and 10.0 g of tetramethyldivinyldisiloxane, add them into a 1L dry and clean three-necked flask, start stirring, evacuate with a vacuum pump, and introduce dry nitrogen at the same time, heat to 60 degrees Celsius and react for 1 hour; add 2.7 g of tetramethylammonium hydroxide to the reaction system, heat to 90 degrees Celsius, continue to react for 1 hour, then heat to 120 degrees Celsius and react for 2 hours; heat the reaction system to 150 degrees Celsius, distill under reduced pressure until no liquid drips out, and continue distillation for 0.5 hours to obtain 306.5 g of siloxane polymer.

[0028] Example 3

[0029] Weigh 544.9 g of tetraphenyltetramethylcyclotetrasiloxane and 10.0 g of tetramethyldivinyldisiloxane, add them into a 1L dry and clean three-necked flask, start stirring, evacuate with a vacuum pump, and introduce dry nitrogen at the same time, heat to 60 degrees Celsius and react for 1 hour; add 2.7 g of phosphazenium amine to the reaction system, heat to 90 degrees Celsius, continue to react for 1 hour, then heat to 120 degrees Celsius and react for 2 hours; heat the reaction system to 150 degrees Celsius, distill under reduced pressure until no liquid drips out, and continue distillation for 0.5 hours to obtain 322.8 g of siloxane polymer.

[0030] Example 4

[0031] 100 g of the siloxane polymer prepared by the method of Examples 1-3, 345 g of polypropylene, 45 g of flaky silicon dioxide (diameter 5 μm, thickness 0.5 μm), 5.0 g of powdered silicon dioxide (particle size D90 is 300 nm), 1.0 g of antioxidant 1010, and 4.0 g of magnesium stearate were pre-mixed and added into an experimental twin-screw extruder with an extrusion port temperature of 200 degrees Celsius and a screw speed of 100 r / min. After extrusion, the extruder was fed into 22°C water for strand cooling and pelletizing. The pelletized material was placed in a vacuum drying oven at 80°C and dried for 6 hours to obtain a polymerized siloxane material 1. The scanning electron microscope image of the flaky layer structure of the silicon dioxide agglomerate is shown in the attached figure. Figure 1 The scanning electron microscope image of material 1 is shown in the attached figure. Figure 2 .

[0032] Example 5

[0033] 250 g of the siloxane polymer prepared by the method of Examples 1-3, 195 g of polypropylene, 35 g of flaky silicon dioxide (diameter 5 μm, thickness 0.5 μm), 15 g of powdered silicon dioxide (particle size D90 is 300 nm), 1.0 g of antioxidant DLTP, and 4.0 g of stearic acid were pre-mixed and added into an experimental twin-screw extruder with an extrusion port temperature of 200 degrees Celsius and a screw speed of 100 r / min. After extrusion, the extruder was fed into 22°C water for strand cooling and pelletizing. The pelletized material was placed in a vacuum drying oven at 80°C and dried for 6 hours to obtain polymerized siloxane material 2.

[0034] Example 6

[0035] 100 g of the siloxane polymer prepared by the method of Examples 1-3, 345 g of polypropylene, 35 g of flaky silicon dioxide (diameter 5 μm, thickness 0.5 μm), 15 g of powdered silicon dioxide (particle size D90 is 300 nm), 1.0 g of antioxidant 168, and 4.0 g of sodium stearate were pre-mixed and added into an experimental twin-screw extruder with an extrusion port temperature of 200 degrees Celsius and a screw speed of 100 r / min. After extrusion, the mixture was sent into 22°C water for strand cooling and pelletizing. The pelletized material was placed in a vacuum drying oven at 80°C and dried for 6 hours to obtain polymerized siloxane material 3.

[0036] Comparative Example 1

[0037] 100 g of the siloxane polymer prepared by the method of Examples 1-3, 345 g of polypropylene, 15 g of powdered silicon dioxide (particle size D90 is 300 nm), 1.0 g of antioxidant 1010, and 4.0 g of magnesium stearate were pre-mixed and added into an experimental twin-screw extruder with an extrusion port temperature of 200 degrees Celsius and a screw speed of 100 r / min. After extrusion, the extruder was fed into 22°C water for strand cooling and pelletizing. The pelletized material was placed in a vacuum drying oven at 80°C and dried for 6 hours to obtain comparative material 2.

[0038] Comparative Example 2

[0039] 445 g of polypropylene prepared by the method of Examples 1-3, 45 g of flaky silicon dioxide (diameter 5 μm, thickness 0.5 μm), 5.0 g of powdered silicon dioxide (particle size D90 is 300 nm), 1.0 g of antioxidant 1010, and 4.5 g of magnesium stearate were pre-mixed and added into an experimental twin-screw extruder with an extrusion port temperature of 200 degrees Celsius and a screw speed of 100 r / min. After extrusion, the mixture was fed into 22°C water for strand cooling and pelletizing. The pelletized material was placed in a vacuum drying oven at 80°C and dried for 6 hours to obtain comparative material 2.

[0040] Tensile strength: refer to GB / T 1040.2-2006 test specimen tensile strength, specimen shape: 1A type; size: 25mm×5mm×1mm; loading rate: 5mm / min; preparation method: injection molding; test five times and take the average value.

[0041] Impact strength: refer to GB / T 1043.1-2008 test specimen notch impact strength, the notch specimen section is 8mm×4mm, V-shaped notch, notch depth is 2mm, pendulum selection is 11J, test five times and take the average value.

[0042] The test results are shown in Table 1.

[0043] Table 1 Summary of formula combinations and material performance test results of embodiments and comparative examples

[0044]

[0045]

[0046] From the above results, it can be seen that the tensile strength of material 1 is 3 times that of polypropylene, and the impact strength is 6.9 times that of polypropylene, indicating that the performance of the composite material prepared by the formula and preparation method of this scheme has been greatly enhanced; as the ratio of flaky silicon dioxide to powdered silicon dioxide increases, the performance of the composite material increases; without adding siloxane polymer, the material performance is close to that of polypropylene. It shows that a good ratio is a key influencing factor in maintaining the "brick-mud" structure of the material, and the good compatibility of siloxane polymer and polyamide plays a good "bridging" role.

[0047] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.

Claims

1. An organosiloxane composition, characterized in that: The weight ratio includes: 10-20% silicon dioxide, 20-50% siloxane polymer, 30-69% polypropylene, 0.1-0.4% antioxidant, and 0.6-0.9% lubricant, wherein the structural formula of the siloxane polymer is:

2. The organosiloxane composition according to claim 1, characterized in that: The silicon dioxide is in the form of flakes and powders, wherein the mass ratio of flakes to powders is 70-90:10-30.

3. The organosiloxane composition according to claim 2, characterized in that: The diameter of flaky silicon dioxide is 4-8 microns, the thickness is 0.3-1 microns, and the particle size D90 of powdered silicon dioxide is 200-600 nanometers.

4. The organosiloxane composition according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010, antioxidant DLTP, and antioxidant 168, or a combination thereof.

5. The organosiloxane composition according to claim 1, characterized in that: The lubricant is a fatty acid or a fatty acid salt.

6. A method for preparing a siloxane polymer according to claim 1, characterized in that: The following steps are involved: S1, add tetraphenyltetramethylcyclotetrasiloxane and tetramethyldivinyldisiloxane into a reactor, start stirring, and react under reduced pressure at 50-60 degrees Celsius for 1-2 hours, while passing nitrogen to remove moisture in the system; S2, adding an organic base catalyst to the reactor of step S1, heating to 70-90 degrees Celsius, reacting for 1-3 hours, then heating to 110-120 degrees Celsius, reacting under reduced pressure for 2-3 hours to obtain a reaction solution; S3, raising the temperature of the reaction solution in step S2 to 140-150 degrees Celsius, removing unreacted materials by evaporation under reduced pressure, and then cooling the reaction product to room temperature to obtain a siloxane polymer.

7. The method for preparing a siloxane polymer according to claim 6, characterized in that: In step S1, the molar ratio of tetraphenyltetramethylcyclotetrasiloxane to tetramethyldivinyldisiloxane is 80-95:

5.

8. The method for preparing a siloxane polymer according to claim 6, characterized in that: In step S2, the organic base is one of tetramethylammonium hydroxide and phosphazene base.

9. The organosiloxane composition according to claim 1, characterized in that: Applications in the following materials: automotive die castings, circuit board insulation materials, silicone packaging materials, and electrical insulation materials.

Citation Information

Patent Citations

  • Aryl-containing polysiloxane and preparation method thereof

    CN101824150A

  • A polypropylene composition, a method of producing the same, and articles made therefrom

    CN101842434A

  • Silicon dioxide / layered inorganic clay composite powder and preparation method thereof

    CN102070919A

  • A toughened shock-resistant PA66 composition

    CN107201031A

  • Preparation method of vinyl-terminated methyl phenyl polysiloxane

    CN112409597A